Premixed Flameless Combustion Of Producer Gas In A Cyclone Combustor - Chanphavong, Lemthong (2019)
Conventional combustion mode of producer gas (PG) encounters flame instability, low burning rate, and dropping in power output due to its low heating content. Flameless combustion is a promising combustion technique for improving performance of the combustion process. However, its application with PG remains much less common. This study aims to investigate premixed flameless combustion of PG. PG derived from a gasification of rubber wood blocks was combusted in a premixed cyclone combustor. Then, numerical simulation was conducted to gain insight into the chemical kinetics processes and its combustion characteristics. Experimental results showed that the optimum combustion process was achieved for the case of inlet nozzle diameter of 30 mm and equivalence ratio of 0.89 with flue gas temperature of 1096.33 K and minimum CO of 133.3 ppm while NOx emission was 402.3 ppm at this operating point. Chemical kinetics analysis and computational fluid dynamics (CFD) simulation were implemented to determine the achievement of flameless combustion based on reactants dilution ratio, Rdil > 0.6, normalized temperature uniformity, Tn < 15%, and its reaction regime. The CFD results also revealed that increasing inlet reactants temperature from 400 K to 700 K was beneficial for more uniformity of temperature distribution, but it resulted in increasing CO from 170 ppm to 401.19 ppm and NO from 12.7 ppm to 58.9 ppm. Increasing the heating value of fuel significantly decreased the temperature distribution uniformity. CO decreased from 170.01 ppm to 21.88 ppm while NO increased from 13 ppm to 795 ppm when increasing heating value from 4 MJ/m3 to 11.6 MJ/m3. For increasing number of the nozzle from 1N to 4N, it slightly decreased the temperature distribution uniformity. CO decreased from 170.01 ppm to 103.249 ppm while NO increased from 12.7 ppm to 47.34 ppm.